Trust in Supervisor as a Mediator of the Relationship Between Perceived Interactional Fairness in Reward Systems and Organizational Commitment - Abdin, Fatmawati; Ismail, Azman; Nor, Azmawaty Mohamad (The South East Asian Journal of Management, 2019)
Research Aims - This study was undertaken to extend existing literature by examining the mediating effect of trust in supervisors in the relationship between perceived interactional fairness in reward systems and organizational commitment. Design/methodology/approach - The SmartPLS method was applied to analyze the survey questionnaire data collected from employees at a national audit department in Malaysia. Research Findings - The results reveal that the effect of perceived interactional fairness in reward systems on organizational commitment is mediated by trust in supervisors. Theoretical Contribution/Originality - This study has proved the effectiveness of perceived interactional fairness as an essential mediating variable in the administration of reward systems. Managerial Implication in the South East Asian context - The findings of this study could help superiors in public organizations to encourage and support their supervisors in implementing good treatment styles for enhancing fairness in making pay decisions and interacting with diverse subordinates. If employees trust their supervisors, it may enhance the effect of employees’ perceived fairness of reward systems on organizational commitment in public organizations in Southeast Asia. Research limitation & implications - This study is limited by its sample, self-report questionnaire scale, and exclusion of several important demographic variables (e.g., gender, age, education, position, and duration of service) in the research model.